The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1200/jco.2022.40.16_suppl.589
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant giredestrant (GDC-9545) plus palbociclib (P) versus anastrozole (A) plus P in postmenopausal women with estrogen receptor–positive, HER2-negative, untreated early breast cancer (ER+/HER2– eBC): Final analysis of the randomized, open-label, international phase 2 coopERA BC study.

Abstract: 589 Background: Endocrine therapy (ET) is the therapeutic mainstay for ER+ BC. Giredestrant is a highly potent, nonsteroidal, oral, selective ER antagonist and degrader (SERD) which has demonstrated robust ER occupancy, is well tolerated, and has previously shown encouraging antitumor activity as monotherapy and in combination with P in metastatic BC. coopERA BC (NCT04436744) evaluated giredestrant in eBC and met its primary endpoint, highlighting superior Ki67 suppression with single-agent giredestrant vs A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…acelERA is a randomized phase II trial of giredestrant vs fulvestrant or aromatase inhibitor that failed to meet its primary endpoint of superior PFS for the study drug [79], although subgroup analysis of patients with baseline ESR1 mutations appeared to show promising effects. Giredestrant did outperform anastrozole in reducing Ki67 expression and inducing complete cell cycle arrest when used as neoadjuvant therapy for previously untreated patients from the coopERA study in postmenopausal women with hormone receptor-positive, HER2 − early breast cancer [80]. Giredestrant is currently explored as first-line therapy for advanced breast cancer and early-stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…acelERA is a randomized phase II trial of giredestrant vs fulvestrant or aromatase inhibitor that failed to meet its primary endpoint of superior PFS for the study drug [79], although subgroup analysis of patients with baseline ESR1 mutations appeared to show promising effects. Giredestrant did outperform anastrozole in reducing Ki67 expression and inducing complete cell cycle arrest when used as neoadjuvant therapy for previously untreated patients from the coopERA study in postmenopausal women with hormone receptor-positive, HER2 − early breast cancer [80]. Giredestrant is currently explored as first-line therapy for advanced breast cancer and early-stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For tumors that are hormonal therapy naïve or first-line therapy, oral SERDs plus CDK4/6 inhibitors are being compared with AIs plus CDK4/6 inhibitors as in AMEERA-5 [87] (amcenestrant), SERENA 4 [88](camizestrant), or with physicians' choice plus CDK4/6 inhibitors as in acelERA Breast Cancer [78] (giredestrant) and in tumors with ESR1 mutation, as in SERENA 6 [89] (camizestrant). In the neoadjuvant setting, oral SERDs are being explored in locally advanced HR + /HER2 − stage III breast cancer against AIs alone as in AMEERA-4 [90] (amcenestrant) or in combination with CDK4/6 inhibitors as in coopERA BC study [80] (giredestrant). Similarly, in the adjuvant treatment of early breast cancer, oral SERDs are being studied against AIs or physicians' choice as in the Lidera Breast Cancer Study [91] (giredestrant) or tamoxifen as in AMEERA-6 [92] (amcenestrant) in HR + /HER2 − stages I-II early breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The coopERA trial is a randomized, phase II neoadjuvant trial of giredestrant versus anastrozole, with the addition of palbociclib in both arms after 14 days of treatment. The final analysis on 201 evaluable patients on the lead-in phase of the study (without palbociclib) has shown a statistically significant reduction in Ki67 after 14 days of treatment with giredestrant compared to AI (relative reduction in geometric Ki67 of − 75% vs − 67%, respectively) [75]. However, giredestrant combined with palbociclib did not show an improvement in terms of pCR rate compared to the control arm.…”
Section: Serds With Basic Amino Side Chainsmentioning
confidence: 97%
“… 76 At the end of the neoadjuvant combination treatment phase, geometric mean relative reduction in Ki67 was again superior in the giredestrant arm at −81% compared with −74%, but there was no difference in the ORR nor pathological complete response rate between the trial arms. 77 …”
Section: Oral Serd Window Trialsmentioning
confidence: 99%
“…76 At the end of the neoadjuvant combination treatment phase, geometric mean relative reduction in Ki67 was again superior in the giredestrant arm at −81% compared with −74%, but there was no difference in the ORR nor pathological complete response rate between the trial arms. 77 In the AMEERA-4 trial, 105 patients with ER positive, HER2 negative early breast cancer with a primary tumor ≥ 1.0 cm and Ki67 ≥ 15% were randomized 1:1:1 to amcenestrant 400 mg daily, amcenestrant 200 mg daily, or letrozole 2.5 mg daily for 2 weeks before surgery. 78 No formal statistical comparisons were performed as the study had closed early due to slow trial enrollment.…”
Section: Oral Serd Window Trialsmentioning
confidence: 99%